The Joint Economic Committee's "Economic Policy Questionaire" - Weisbrod, Burton A. (The Review of Economics and Statistics, 1960)
In September I958, the Subcommittee on Stabilization of the Joint Committeeof the U.S. Congress distributed an Economic Policy Questionnaire among some I500 college and university economists. The replies on the 65 questionnaires which were returned have been tabulated and appear in a report which has recently become available. It is the purpose of this note to discuss some of the significant aspects of the questionnaire.